ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN (Studi Pada CV. Yudistira Motor Kaliwungu Kabupaten Kendal) - Muhamad Maghfur, 07.05.51.0109; Suharmanto, Toto (Students Journal of Economic and Management, 2012)
Emulation of[is effort in the field of motorbike workshop especially in nations is expanding very quickly. company of the Workshop have to be more pay attention the quality of service activities which they sell. Concept of is quality of service have come to very dominant factor to efficacy of company, because if customer client or consumer feel that quality of well accepted service or it to hence will feel trust and have commitment become customer which is loyal. Pursuant to the mentioned hence writer try to lift research with title âAnalisis Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan (Studi Pada CV. Yudistira Motor Kaliwungu Kabupaten Kendal) â. Research concerning influence of is quality of service to customer loyalties at CV. Yudistira Motor Kaliwungu Kabupaten Kendal take 80 responder with significant level 5%, used by data is primary data, data analysis use analysis qualitative and quantitative which cover validity test, test reliabilities, doubled regression, hypothesis test and determination coefficient. Pursuant to variable influence data analysis of is quality of service to customer loyalties can be taken by the following conclusion : equation of yielded by doubled linear regression of examination by partial obtained there are positive influence and significant between quality of service which in the form of extant to customer loyalties CV. Yudistira Motor Kaliwungu. There are positive influence and significant between quality of service which in the form of mainstay to customer loyalties CV. Yudistira Motor Kaliwungu. There are positive influence and significant between quality of service which in the form of comments to customer loyalties CV. Yudistira Motor Kaliwungu. There are positive influence and significant between quality of service which in the form of certainty to customer loyalties CV. Yudistira Motor Kaliwungu. There are positive influence and significant between quality of service which in the form of caring to customer loyalties CV. Yudistira Motor Kaliwungu. Equal to 89 % customer loyalties CV. Yudistira Motor Kaliwungu can influence by quality of service which in the form of is extant, mainstay, comments, caring and certainty. Key words : extant, mainstay, comments, certainty and customer loyalties.